Prediction of Occult Lymph Node Metastasis in Head and Neck Cancer with CD31 Vessel Quantification. (February 2019) - Mermod, Maxime; Bongiovanni, Massimo; Petrova, Tatiana; Goun, Elena; Simon, Christian; Tolstonog, Genrich; Monnier, Yan
Objective: The management of occult lymph node metastasis (LNM) in head and neck squamous cell carcinoma has been a matter of controversy for decades. The vascular density within the tumor microenvironment, as an indicator of ongoing angiogenesis, could constitute an attractive predictor of LNM. The use of the panvascular endothelial antibody CD31 as a marker of occult LNM has never been reported. The aim of this study was to assess the predictive value of CD31 microvascular density for the detection of occult LNM in squamous cell carcinoma of the oral cavity and oropharynx. Study Design: Case series with chart review. Setting: Tertiary university hospital. Subjects and Methods: Intra- and peritumoral microvascular density values were determined in 56 cases of squamous cell carcinoma of the oral cavity (n = 50) and oropharynx (n = 6) with clinically negative necks using the CD31 marker. Statistical associations of CD31 microvascular densities with clinicopathologic data were then established. Results: Peritumoral CD31 microvascular density was significantly associated with occult LNM in multivariate analysis ( P < .01). Recursive partitioning analysis for this parameter found a cutoff of 19.33, which identified occult LNM with a sensitivity of 91%, a specificity of 65%, a positive predictive value of 40%, a negative predictive value of 97%, and an overall diagnostic accuracy of 71%. Conclusion: Peritumoral CD31 microvascular density in primary squamous cell carcinoma of the oral cavity and oropharynx allows accurate prediction of occult LNM.